华北地区冬小麦田水热、二氧化碳和甲烷湍流输送特征的实验研究 - 葛红星; 张宏升; 罗帆; 蔡旭晖; 宋宇; 康凌; 霍庆 (地球物理学报, 2016)
本文利用2012年4月30日至5月10日华北地区大气湍流实验资料,分析了冬小麦田下垫面温度、湿度、二氧化碳(CO_2)和甲烷(CH_4)的湍流统计和输送特征,利用涡旋相关法计算的CH_4通量值确定了松弛涡旋累积(REA)法计算CH_4通量的经验系数.结果表明,不稳定层结下,温度、湿度、CO_2和CH_4的归一化标准差随稳定度参数z/L的关系满足-1/3幂次关系.热量、水汽和CO_2水平方向的湍流输送和垂直方向的比值与稳定度参数z/L存在一定的相关关系,但CH_4没有类似特征.实验期间,感热通量数值较低,潜热通量较高;CO_2在夜间表现出微弱的向上输送,其余时段为向下输送,可以认为实验站所在地区是碳汇;CH_4的湍流输送整体为向下输送,无明显的日变化规律,可以认为是CH_4汇.利用松弛涡旋累积法获取CO_2和CH_4通量的参数取值分别为0.61和0.30. Based on the turbulent observations during April 30 and May 10 2012, this work investigated statistical characteristics of atmospheric turbulent and water, heat, carbon dioxide (CO2) and methane (CH4) transport in North China. The empirical coefficient used to calculate the flux of CH4 in the Relaxed Eddy Accumulation (REA) method was simulated. The results show that in unstable conditions, the normalized standard deviations of temperature, humidity, CO2 and CH4 are related to z/L following the "-1/3 power law". The ratios between horizontal transport and vertical transport of heat, water vapor and CO2 are related to z/L, but CH4 has no similar relationship. Sensible heat flux is quite low while latent heat flux is relatively high. CO2 flux is slightly above zero during nighttime and below zero during daytime, indicating that the observed area is a carbon sink. CH4 flux is mainly below zero, indicating that the observed area is a methane sink. The values of the empirical coefficients used to calculate the flux of CO2 and CH4 in REA method are 0. 61 and 0. 30, respectively. 环保部公益性行业科研专项项目,国家自然科学基金 SCI(E) EI 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) ge_star@163.com; hsdq@pku.edu.cn 4 1235-1248 59